If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -8) + 9 = 12x + -23 Reorder the terms: 4(-8 + 3x) + 9 = 12x + -23 (-8 * 4 + 3x * 4) + 9 = 12x + -23 (-32 + 12x) + 9 = 12x + -23 Reorder the terms: -32 + 9 + 12x = 12x + -23 Combine like terms: -32 + 9 = -23 -23 + 12x = 12x + -23 Reorder the terms: -23 + 12x = -23 + 12x Add '23' to each side of the equation. -23 + 23 + 12x = -23 + 23 + 12x Combine like terms: -23 + 23 = 0 0 + 12x = -23 + 23 + 12x 12x = -23 + 23 + 12x Combine like terms: -23 + 23 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 36/(6/1-1/3) | | 7x+6x-1=0 | | 5z-8+2z=34 | | 45x+2155x-84=44(50x+55) | | 12+g=55 | | 6x=68 | | h/11=-11 | | 2(4x+3)+74=10x+2-2x+78 | | (3x/6)-(x-2/2)=(x-1/4) | | 8-c=3 | | X(x-8)=3(x-3) | | 1936x-2244=44(44x-51) | | 6x-2-3x-20=x | | a+9=27 | | 794=114+8b | | 24g-22=626 | | 6x+2-3x+20=x | | b/7+184=199 | | 2b+4=6b-4 | | 2x^2+19x-7.5=0 | | (3x^(2/3))+(10x^(1/3))=8 | | 17=-13+x | | 8/15x=8-2/15 | | 19T-(-25)=158 | | 7b-3b=36 | | 16x-9=4(4x+7) | | 3/x=(9/8x)+3 | | 4x-3=6y+8 | | 15=K/5+23 | | 52=6N-2 | | 7N-22=13 | | 6+2+3+20=x |